Media Framing of Identity Politics through Prejudice and Stereotype Towards the 2024 Election - Semuel Akihary; Rustono Farady Marta; Hana Panggabean (Jurnal Kajian Jurnalisme, 2023)
This research discusses identity politics through prejudice and stereotype toward the 2024 presidential election. Identity politics refers to the way politics works in determining and classifying identities. In its development, especially in the last few elections, identity politics is full of harmful content that divides various elements of society. This study aims to analyze the media framing raised in three perspectives of online media, namely, Mediaindonesia.com, Detik.com, and Kompas.com. This study used a qualitative method using Pan & Kosicki’s framing theory. The study results show that Mediaindonesia.com's news content aims to provide normative justification while safeguarding the integrity of the NasDem party as a "movement for change." It is achieved by countering any negative and intolerant stigmas associated with identity politics issues related to the party's endorsed presidential candidate. In contrast, Detik.com is more direct in identifying social polarization categories about identity politics, highlighting the disparities between opposing views through carefully selected source quotes and rhetorical devices. Meanwhile, Kompas.com tends to take a more neutral stance, prioritizing the electability of candidates and navigating the balance between tolerance and intolerance. Framing analysis allows readers to maintain a critical perspective and comprehend how the media presents an issue in order to accomplish specific goals.